Factors Affecting Personal Income Tax Compliance Behavior of Expatriates Working in Thailand - Puriboriboon, Pratoomma; Saetao, Jaruwan (Rajapark Journal, 2023)
This research aimed to study the influence of tax knowledge, fairness of tax system perception, and law enforcement perception on tax compliance behavior of foreigners who work in Thailand, using satisfaction with paying personal income taxes as a passive variable. A questionnaire was used to collect data from 206 participants. The data were analyzed by frequency, percentage, mean, standard deviation, confirmatory factor analysis, and structural equation modeling (SEM). The findings revealed that the model and empirical data were consistent and that tax knowledge and fairness of tax system perception directly influenced satisfaction with paying personal income taxes. Law enforcement perceptions had no effect on satisfaction with paying personal income taxes. However, satisfaction with paying personal income taxes had a direct influence on tax compliance behavior. Moreover, the study showed that tax knowledge, fairness of tax system perception, and law enforcement perception had a positive indirect influence on tax compliance behavior through satisfaction with paying personal income taxes.